2009
DOI: 10.1007/s11244-009-9186-4
|View full text |Cite
|
Sign up to set email alerts
|

Low-Temperature Complete Oxidation of Ethyl Acetate Over CeO2-Supported Precious Metal Catalysts

Abstract: Catalytic combustion of ethyl acetate was investigated over various CeO 2 -supported precious metal catalysts prepared by impregnation method, and the effect of reduction treatment on the activity was examined. Among the catalysts tested, Ru/CeO 2 achieved the highest activity for ethyl acetate combustion, and the activity was almost unchanged by the heat treatment in a hydrogen atmosphere. In the cases of Pt/CeO 2 , Pd/CeO 2 , and Rh/ CeO 2 , the catalytic activity was enhanced by the reduction treatment at 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 21 publications
1
22
0
Order By: Relevance
“…Accordingly, a correlation between the catalytic activity (both per g of the catalyst per second or TOF) and the reducibility is clearly visible for these catalysts. Mitsui et al [41] studied oxidation of ethyl acetate over CeO 2 -supported metal (Ru, Pt, Pd) catalysts and suggested that metal species reducible at lower temperatures should be responsible for the high activity. In fact, the reduction of ruthenium oxide on CeO 2 was initiated at lower temperature than in the case of the other metals, resulting in the highest activity.…”
Section: Catalystmentioning
confidence: 99%
“…Accordingly, a correlation between the catalytic activity (both per g of the catalyst per second or TOF) and the reducibility is clearly visible for these catalysts. Mitsui et al [41] studied oxidation of ethyl acetate over CeO 2 -supported metal (Ru, Pt, Pd) catalysts and suggested that metal species reducible at lower temperatures should be responsible for the high activity. In fact, the reduction of ruthenium oxide on CeO 2 was initiated at lower temperature than in the case of the other metals, resulting in the highest activity.…”
Section: Catalystmentioning
confidence: 99%
“…1 [21][22][23][24][25][26][27][28][29][30]. In this chapter, the performances of the Ru/CeO 2 catalysts prepared from various CeO 2 powders were compared in terms of the activity for aerobic oxidation of benzyl alcohol as a model reaction.…”
Section: Aerobic Oxidation Of Benzyl Alcohol On Ru/ceo 2 Prepared Fromentioning
confidence: 99%
“…water [25,26], ammonia synthesis [27], N 2 O decomposition [21], complete oxidation of ethyl acetate and propylene [28,29], and other reactions. Recently, Ce 1-x Ru x O 2-d solid solution was reported as a new oxygen storage material [30].…”
mentioning
confidence: 99%
“…Catalytic oxidation is considered one of the most effective techniques for VOC removal, since the total oxidation of diluited fuel occurs at relatively low temperatures, and this leads to low emissions of NO x and unburned fuels [8][9][10][11]. This abatement technique is highly versatile, and offers the possibility of treating waste streams with different VOC concentrations and effluent flow rates [2][3][4].…”
Section: Introductionmentioning
confidence: 99%